Thermal and structure analysis based on exfoliation of clay in thermosensitive polymer by in-situ polymerization - Mohammed, Marwah Noori; Kamal, Yusoh; Jun Haslinda, Haji Sharifuddin (Gadjah Mada University, 2020)
Poly(N-vinylcaprolactam) (PNVCL) offers superior characteristics as a thermoresponsive polymer for various potential applications. An attractive procedure, namely in-situ polymerization, was used to prepare NVCL/clay nanocomposite in different clay ratios. Organo-modified clay as C20 and B30 were employed in a range between 1–5% based on weight. Thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR) were used to study thermal decomposition and to assess bond conversion during polymerization of the nanocomposite. This research was conducted to study PNVCL characteristics with the addition of clay as a nanocomposite. The stretch mode of the carboxylic group (C=O) and (C=C) was present in the band range about ~1635 cm–1 for the C20, but it was ranging between 1640 to 1664 cm–1 for the B30 of the nanocomposite. It was observed that the decomposition was different for each type of organoclay and the temperature peaked at 30 to 800 °C, to measure the degradation points at 5, 10, and 50%. Comparison results for FTIR and TGA showed that the best nanocomposite was found in the C20 (3%) case.